Guidelines for the management of bullous pemphigoid. - Wojnarowska, F; Kirtschig, G; Highet, A; Venning, V; Khumalo, N (2002)
These guidelines have been prepared for dermatologists on behalf of the British Association of Dermatologists. They present evidence-based guidance for treatment, with identification of the strength of evidence available at the time of preparation of the guidelines and a brief overview of epidemiological aspects, diagnosis and investigation. The guidelines reflect data available from Medline, Embase, the Cochrane library, literature searches and the experience of the authors of managing patients with bullous pemphigoid in special and general clinics for over 10 years. However, caution should be exercised in interpreting the data obtained from the literature because only six randomized controlled trials are available involving small groups of patients.